Keanekaragaman Fungi Entomopatogen Lokal Asal Cagar Alam Gunung Tukung Gede - Rida Khastini; Nani Maryani; Iing Dwi Lestari; Ika Rifqiawati; Nada Ummatul Millah (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Background: Entomopathogenic fungi are one of the potential biodiversity assets to be used as biological control agents. However, information about the diversity of entomopathogenic fungi, especially in the Gunung Tukung Gede (GTG) nature reserve is very limited. The purpose of this study was to provide information on the biodiversity of entomopathogenic fungi in the GTG nature reserve. Methods: The entomopathogenic fungi were explored from 3 different stations: primary forest, secondary forest and disturbed forest. Entomopathogenic fungi were isolated identified both macroscopically and microscopically. Results: A total of 15 specimens of entomopathogenic fungi consisting of 5 families and 8 types of fungi successfully isolate. The entomopathogen fungi were Basidiobolus haptosporus, Beauveria bassiana., Metarhizium aniesophalie, Paecilomyces sp., Aschersonia sp., Aspergillus sp. 1, Aspergillus sp.2, and Septobasidium sp. These fungi infect insect hosts from the orders Lepidoptera, Hemiptera and Homoptera. The index of the diversity of entomopathogenic fungi at 3 consecutive stations is 1.5495; 1.3322; and 0.6365 (medium category). Conclusions: The GTG Nature Reserve has a unique diversity of entomopathogenic fungi. Therefore, further research is needed in order to determine the diversity and potential utilization of the existing entomopathogenic fungi.